2008
DOI: 10.1021/ja804039c
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Molecular-Level Segregation of Complex Alkane Mixtures in Metal−Organic Frameworks

Abstract: Metal-organic frameworks (MOFs) are a new class of nanoporous materials that have good stability, high void volumes, and welldefined tailorable cavities of uniform size.1 MOFs consist of metal oxide vertices interconnected by rigid or semirigid organic molecules having terminal functional groups that bind to the metal corners. The pores of MOFs can be systematically varied by a judicious choice of linker molecules and/or metal corners. Moreover, the higher void volumes in comparison to, for example, zeolites c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 21 publications
1
88
0
Order By: Relevance
“…This allows one to check and study 'segregation' of molecules. [92] Figures 3 and 11 have been made using RASPA and VTK. To visualise molecules inside the structure, the pore walls can be rendered transparent.…”
Section: Visualisationmentioning
confidence: 99%
“…This allows one to check and study 'segregation' of molecules. [92] Figures 3 and 11 have been made using RASPA and VTK. To visualise molecules inside the structure, the pore walls can be rendered transparent.…”
Section: Visualisationmentioning
confidence: 99%
“…Dubbeldam et al [38] have reported using grand canonical Monte Carlo simulations (GCMC), that MOF 1 presents two energetically different sites of adsorption. At low loading, the bulkier molecules adsorb along the 7.5 Â 7.5 Å 1D channels, preferentially near the ''boxes'' formed by the ''BDC'' ligands.…”
Section: Modeling Adsorption Equilibriummentioning
confidence: 99%
“…The fitted parameters obtained are reported in Table 2. We take site A to be the one with higher Langmuir constant, which according to Dubbeldam et al [38] represents sorption along the 7.5 Â 7.5 Å 1D channels near the ''boxes''. The lines in Fig.…”
Section: Pure Component Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Finally, PSi is readily functionalized by a large variety of molecular structures [25][26][27][28][29] and is highly chemically reactive. [30] It has also been suggested that nanoporous materials can preferentially adsorb different species of organic molecules, [31] indicating that the right preparation of PSi could serve as a selective detector of explosive molecules.…”
Section: Introductionmentioning
confidence: 99%